Comparison between the distributions of land-locked Atlantic salmon Salmo salar L. and three-spined stickleback Gasterosteus aculeatus L. in the river Namsen, Norway - Ole Kristian Berg (Fauna Norvegica)
The land-locked salmon Salmo salar L. in the river Namsen is found up-stream to a waterfall situated 290 m above s.l. It is found both above and below the Trongfoss waterfall in the main river. The three-spined stickleback Gasterosteus aculeatus L. in the river Namsen is found as far up as about 130 m above s.l., below the Trongfoss waterfall, although in some of the tributaries it extends higher up than the land-locked salmon. An explanation of the differing distribution of the two species is that the salmon immigrated into the river before about 9500 B.P. (years before present), wheras the three-spined stickleback immigrated after 9500 B.P. but before 9100 B.P.